Baseline Survey on Existing Status of Fried Potato Chips From Processing to Marketing in Selected Locations of Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
The baseline survey was conducted with a view to generate information on existing status of fried potato chips from processing to marketing in selected locations of Bangladesh. The baseline information was collected from seven selected districts namely Dhaka, Gazipur, Tangail, Mymensingh, Bogura, Munshigonj and Jashore. Fifteen hawkers and five producers were randomly selected to collect the information by the pre-tested questionnaire from each location both from producer to consumer. Most of the hawkers of Bogura was above 40 years old (80%) followed by Dhaka who were 25-39 years old (60%). In Bangladesh, eighty percent people were above 40 years old engaged in processing fried potato chips. All aged people in Bogura preferred fried potato chips (100%) whereas maximum child in Jashore (80%) liked fried potato chips. Bogura and Munshigonj people were unknown about healthiness knowledge of fried chips consumption. Bogura, Jashore and Munshigonj processors/producers were hawkers and they prepared the product and distributed the products to the market or direct involved in sale. Fried chips processing people in the survey area used deep frying technique (100%). Soya bean oil used for deep oil frying of potato chips by 80% small processors. Most of the respondents changed their frying oil during frying when frying oil turned into cloudy.Bangladesh J. Agril. Res. 45(2): 137-144, June 2020